Investigação da atividade anti-agregante plaquetária in vitro de peptídeos inibidores da dissulfeto isomerase protéica - etapa 2 - SOUSA, Hiran Reis (2016)
Recent researches have emphasized the importance of redox mechanisms for platelet function modulation. The platelet surface contains a large variety of integrin receptors and other molecules presenting functional thiol groups in their structures, which are potential targets for redox regulation. Among these various thiol-containing proteins, integrin αIIbβ3 stands out for being the convergence path of platelet activation induced by various agonists. Activation of αIIbβ3 integrin is catalyzed by protein disulfide isomerase (PDI) through an essential conformational change leading to the exposure of fibrinogen-binding site. Thus, PDI has been shown to be an important target for the development of antiplatelet drugs. In recent years, many studies have described substances from plan (DE A. PAES et al., 2011), as well as synthetics that are capable of inhibiting PDI. In a previous study of our research group has shown that the synthetic peptide CxxC, which contains the redox motif of PDI in its original sequence CGHC, inhibited reductase activity of this enzyme, effect not observed with AxxA peptide, whose cysteines were replaced with alanine and Scr peptide, which contains the same aminoacids from CxxC peptide, but under random sequence. It has been also demonstrated that CxxC peptide was the only to reduce by 30% ADP-induced aggregation (5μM) in platelet rich plasma, an effect apparently mediated by the association of CxxC and PDI at platelet surface. Thus, in this work, we further assessed the effects of CxxC and its control peptides on platelet aggregation. Washed human platelets were incubated with CxxC peptide at concentrations of 3, 6 and 10 μM, resulting in a dose-dependent inhibition of maximum aggregation activated by thrombin (0.02 U/mL) at 25, 60 and 74%, respectively with IC50 of 6.13 ± 1.09 μM. The presence of control peptides did not produce any inhibitory effect. CxxC peptide also reduced the activation of αIIbβ3 integrin at platelet surface, but did not affect the expression of the markers CD 62-P and CD 63. Control peptides did not alter the expression of these markers. Analysis by mass spectrometry of the interaction of recombinant human PDI with the peptide showed that only CxxC peptide associated with the redox Cys400 of a’ motif of PDI, which has been considered essential for platelet aggregation. Together, these results demonstrate that CxxC peptide reduces platelet aggregation by association with PDI and can be further used as a model for the development of new antithrombotic drugs.